Treat me well or will resist: Uptake of mobile genetic elements determine the resistome of corynebacterium striatum - Leyton, Benjamin; Ramos, Juliana Nunes; Baio, Paulo Victor Pereira; Veras, João Flávio Carneiro; Souza, Cassius; Burkovski, Andreas; Mattos-Guaraldi, Ana Luíza; Vieira, Verônica Viana; Abanto Marin, Michel (International Journal of Molecular Sciences, 2021)
Corynebacterium striatum, a bacterium that is part of the normal skin microbiota, is also an opportunistic pathogen. In recent years, reports of infections and in-hospital and nosocomial outbreaks caused by antimicrobial multidrug-resistant C. striatum strains have been increasing worldwide. However, there are no studies about the genomic determinants related to antimicrobial resistance in C. striatum. This review updates global information related to antimicrobial resistance found in C. striatum and highlights the essential genomic aspects in its persistence and dissemination. The resistome of C. striatum comprises chromosomal and acquired elements. Resistance to fluoro-quinolones and daptomycin are due to mutations in chromosomal genes. Conversely, resistance to macrolides, tetracyclines, phenicols, beta-lactams, and aminoglycosides are associated with mobile genomic elements such as plasmids and transposons. The presence and diversity of insertion sequences suggest an essential role in the expression of antimicrobial resistance genes (ARGs) in genomic rearrangements and their potential to transfer these elements to other pathogens. The present study underlines that the resistome of C. striatum is dynamic; it is in evident expansion and could be acting as a reservoir for ARGs.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Antibiotic resistance genes; Corynebacterium striatum; Emerging pathogen; Insertion sequences; MLS phenotype; Multidrug resistance mechanisms; PTP10 plasmid; Resistome; Tn5432; Trans-posons